In vitro neutrophil migration is associated with inhaled corticosteroid treatment and serum cytokines in pediatric asthma - Lemmel, Solveig; Weckmann, Markus; Wohlers, Anna; Jirmo, Adan Chari; Grychtol, Ruth; Ricklefs, Isabell; Nissen, Gyde; Bachmann, Anna; Singh, Shantanu; Caicedo, Juan; Bahmer, Thomas; Hansen, Gesine; et al. (Frontiers in Pharmacology, 2022)
Abstract: Background: Different asthma phenotypes are driven by molecular endotypes. A Th1-high phenotype is linked to severe, therapy-refractory asthma, subclinical infections and neutrophil inflammation. Previously, we found neutrophil granulocytes (NGs) from asthmatics exhibit decreased chemotaxis towards leukotriene B4 (LTB4), a chemoattractant involved in inflammation response. We hypothesized that this pattern is driven by asthma in general and aggravated in a Th1-high phenotype. Methods: NGs from asthmatic nd healthy children were stimulated with 10nM LTB4 / 100nM N-formylmethionine-leucyl-phenylalanine and neutrophil migration was documented following our prior SiMA (simplified migration assay) workflow, capturing morphologic and dynamic parameters from single-cell tracking in the images. Demographic, clinical and serum cytokine data were determined in the ALLIANCE cohort. Results: A reduced chemotactic response towards LTB4 was confirmed in asthmatic donors regardless of inhaled corticosteroid (ICS) treatment. By contrast, only NGs from ICS-treated asthmatic children migrate similarly to controls with the exception of Th1-high donors, whose NGs presented a reduced and less directed migration towards the chemokines. ICS-treated and Th1-high asthmatic donors present an altered surface receptor profile, which partly correlates with migration. Conclusions: Neutrophil migration in vitro may be affected by ICS-therapy or a Th1-high phenotype. This may be explained by alteration of receptor expression and could be used as a tool to monitor asthma treatment. Keywords: Neutrophil Granulocytes, migration, LTB4, fMLP, high-content image analysis, single-cell analysis